The Validity and Reliability of Knowledge and Family Support Research on Working Mothers' Exclusive Breastfeeding - Indah Sulistyowati (GLOBAL HEALTH SCIENCE GROUP, 2025)
For the first six months of an infant's life, WHO and UNICEF recommend exclusive breastfeeding. After that, supplemental foods should be introduced, and breastfeeding should continue until the child is two years old. In 2022, only 67.96% of Indonesians engaged in exclusive breastfeeding, a decline from 69.7% in 2021. This indicates that enhanced support is necessary to increase this coverage. By investigating working mothers' knowledge of exclusive breastfeeding and their families' support for it in Semarang City, the study seeks to evaluate the validity and reliability of the questionnaire. A sample of working women in Semarang City with children between the ages of six and twelve months participated in this study, which employed a quantitative analytical research methodology. Convenience sampling was employed to collect data from 35 working mothers with children aged 6 to 12 months. The women received a questionnaire consisting of 15 inquiries regarding familial support for exclusive breastfeeding and 15 remarks concerning their comprehension of exclusive breastfeeding. Data analysis for the validity test uses Pearson Bivariate correlation, while for the reliability test, it uses Cronbach's Alpha. With a Cronbach's alpha of 0.826 and a Pearson correlation coefficient ranging from 0.418 to 0.733, the study's findings showed that the exclusive breastfeeding knowledge questionnaire was both valid and reliable, surpassing the r table value of 0.334. A Cronbach's alpha of 0.811 and a Pearson correlation coefficient ranging from 0.380 to 0.676, which exceeded the r table value of 0.334, indicated that the family support questionnaire was valid and reliable for exclusive breastfeeding. The study's findings indicated that the knowledge questionnaire on exclusive breastfeeding and the family support questionnaire for exclusive breastfeeding were both valid and reliable.